An Assessment of Myotube Morphology, Matrix Deformation, and Myogenic mRNA Expression in Custom-Built and Commercially Available Engineered Muscle Chamber Configurations - Jones, Julia M.; Player, Darren J.; Martin, Neil R. W.; Capel, Andrew J.; Lewis, Mark P.; Mudera, Vivek (Frontiers in Physiology, 2018)
There are several three-dimensional (3D) skeletal muscle (SkM) tissue engineered models reported in the literature. 3D SkM tissue engineering (TE) aims to recapitulate the structure and function of native (in vivo) tissue, within an in vitro environment. This requires the differentiation of myoblasts into aligned multinucleated myotubes surrounded by a biologically representative extracellular matrix. In the present work, a new commercially available 3D SkM TE culture chamber manufactured from polyether ether ketone (PEEK) that facilitates suitable development of these myotubes is presented. To assess the outcomes of the myotubes within these constructs, morphological, gene expression and extra-cellular matrix remodeling parameters were compared against a previously published custom-built model. No significant differences were observed in the morphological and gene expression measures between the newly introduced and the established construct configuration, suggesting biological reproducibility irrespective of manufacturing process. However, TE SkM fabricated using the commercially available PEEK chambers displayed reduced variability in both construct attachment and matrix deformation, likely due to increased reproducibility within the manufacturing process. The mechanical differences between systems may also have contributed to such differences, however investigation of these variables was beyond the scope of the investigation. Though more expensive than the custom-built models, these PEEK chambers are also suitable for multiple use after autoclaving. As such this would support its use over the previously published hand-made culture chamber system, particularly when seeking to develop higher-throughput systems or when experimental cost is not a factor.